Randomized, Open-Label, Two-Way Crossover Study To Compare The Bioequivalence Of Two Formulations Of Esomeprazole In Healthy Male Volunteers (KYAMC Journal, 2017)
A crossover-randomized bioequivalence study of two oral formulations of esomeprazole (40 mg) capsules were carried out in 16 healthy male Bangladeshi volunteers. The test and reference formulations were PRONEX (Drug International Ltd, Bangladesh) and NEXIUM (AstraZeneca AB, Sweden), respectively. Each tablet was administered with 150 mL of water to subjects after overnight fasting on 2 treatment days separated by 1 week washout period. After dosing, serial blood samples were collected for a period of 24 hours. The plasma concentrations of esomeprazole were estimated using a validated HPLC method. The pharmacokinetic parameters Cmax, Tmax, AUC0g24h, t1/2, and Kel were determined. The mean (± SD) AUC0g24h for esomeprazole of test drug PRONEXTM for 16 volunteers was 1509 (± 546) ng.hr/mL whereas it was 1622 (± 589) ng.hr/mL for esomeprazole of NEXIUMTM. The relative bioavailability (PRONEXTM/NEXIUMTM ratio) was 93%. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of esomeprazole of test drug were 1653 (± 706) ng/mL, 2.13 (± 0.81) hours, 2.00 (± 0.61) hour and 0.3465 respectively. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of esomeprazole of reference drug were 1820 (± 877) ng/mL, 2.80 (± 0.67) hours, 2.14 (± 0.55) hour and 0.3238 respectively. The 90% CI for the test and reference drugs were found within the acceptance range of 80-125%. In conclusion, PRONEX is bioequivalent to NEXIUM in terms of absorption.KYAMC Journal Vol. 4, No.-1, July 2013, Page 326-330